Exploring Blockchain Adoption in Food Safety: A Dual-Stakeholder Perspective Using the UTAUT Model - Huang, Jie; Fang, Fang; Leong, Yee Choy; Yiing, Lee Shin (Journal of Ecohumanism, 2025)
Blockchain adoption in the food industry will bring a major shift in business operations. This study delivers a two-level stakeholder comparison between enterprises and consumers on which group prioritises what while adopting blockchain technology. The study uses a two-level empirical approach with 150 participants from each group, extending the Unified Theory of Acceptance and Use of Technology (UTAUT) to trust. The findings show that enterprise managers prioritise blockchain performance benefits, including cost reduction, process optimisation, and supply chain transparency to meet organisational efficiency goals. However, consumers trust blockchain’s traceability and accountability to assure food safety. This differentiation emphasises targeted blockchain implementation and marketing initiatives. The study emphasises performance and trust. However, sample size restrictions and convenience sampling are addressed. UTAUT is extended by emphasising trust in safety as a key factor in the food business, providing managers and policymakers with practical insights to boost blockchain adoption